Ischemic preconditioning: exploring local ergogenic mechanisms in non-fatiguing voluntary contractions - Allois, Ruben; Pertusio, Raffaele; Pagliaro, Pasquale; Roatta, Silvestro (Frontiers in Physiology, 2025)
BackgroundIPC has been suggested to boost skeletal muscle performance, though its effectiveness remains controversial. This study evaluates whether IPC influences local hemodynamic responses and surface electromyographic (sEMG) activity during non-fatiguing voluntary sustained and intermittent contractions.MethodsTen male participants were subjected to IPC (3 cycles, 5-min ON/5-min OFF right arm ischemia, cuff pressure: 250 mmHg) and SHAM (same protocol at 20 mmHg) in two different sessions. Near-infrared spectroscopy was used to monitor tissue oxygenation (TOI) and deoxy-hemoglobin (HHb) in extensor and flexor forearm muscles. sEMG was also recorded. Measurements were taken during sustained (20-s duration) and intermittent (5 s ON/5 s OFF) isometric contractions at 20, 30, and 40% of the maximal voluntary contraction. These non-fatiguing exercise tasks were performed before and 30 min after the IPC/SHAM intervention.ResultssEMG exhibited a significant increase post vs. pre-treatment in both IPC and SHAM in extensors. A significant decrease in TOI at rest was noted pre vs. post-treatment for both IPC and SHAM (p < 0.01). In general, no main effect of treatment was observed, except for HHb changes during contraction in extensor muscles, associated with no effect of time and no time-treatment interaction. All variables exhibited a main effect of force level (p < 0.05), with no interaction with treatment or time.ConclusionIPC had no effect on hemodynamic and electromyographic variables during sustained and intermittent handgrip. These results do not support IPC-related ergogenic effects at the muscle level, aligning with previous findings on electrically stimulated contractions.